Elementary real and complex analysis - Shilov, G. E. (Dover Publications, 1996)
Excellent undergraduate-level text offers coverage of real numbers, sets, metric spaces, limits, continuous functions, series, the derivative, higher derivatives, the integral and more. Each chapter contains a problem set (hints and answers at the end), while a wealth of examples and applications are found throughout the text. Over 340 theorems fully proved. 1973 edition.
"[A]n unabridged, corrected republication of ... Volume 1 of the two-volume course 'Mathematical Analysis'", originally published in English: Cambridge, Mass. : MIT Press, 1973
Includes index.
Keywords: Mathematical analysis.; elektronické knihy; electronic books